Preparing integrated STEM educators in PNG: the enabling and constraining factors - Matthew Readette; Kainaro Kravia; John Hagoya; Jonika Havave; Savitha DeBritto; Jeffrey Ambelye; Agewa Zeming; Prisilla Sakopa; Terri Bourke; Vinesh Chandra; Denise Beutel; Dann Mallet (Discover Education)
Abstract Science, technology, engineering, and mathematics education is a high priority in many countries, seen to enable future economic growth and competitiveness. An integrated STEM approach seeks to combine these disciplines to solve real-world problems. Teachers play a central role in this endeavour. This paper reports on a research project which evaluated the effectiveness of a postgraduate science teacher education course in preparing future teachers as integrated Science, Technology, Engineering and Mathematics (STEM) educators. The study was conducted at a University in Papua New Guinea that specialises in teacher training and was partially funded by the Australian Government. We conducted 11 interviews to determine stakeholders’ current understandings of integrated Science, Technology, Engineering and Mathematics in education, what enables and constrains STEM education practices; and how teacher training could be improved in Papua New Guinea. Margaret Archer’s emergent properties were used as a robust theoretical frame to analyse the personal, structural and cultural conditions that enable and/or constrain STEM practices within this country. While some enablements were present, findings revealed a broad lack of understanding about integrated Science, Technology, Engineering and Mathematics, as well as significant structures that inhibited STEM practices. Recommendations are made which include a coordinated national approach to increase understanding of integrated Science, Technology, Engineering and Mathematics, and teacher education for integrated Science, Technology, Engineering and Mathematics.